Creative destruction and productive preemption - Pehr-Johan Norbäck; Lars Persson; Roger Svensson (Center for Economic Studies and ifo Institute (CESifo), 2013)
We develop a theory of innovation for entry and sale into oligopoly, and show that inventions of higher quality are more likely to be sold (or licensed) to an incumbent due to strategic product market effects on the sales price. Such preemptive acquisitions by incumbents are shown to stimulate the process of creative destruction by increasing the entrepreneurial effort allocated to high-quality invention projects. Using data on patents granted to small firms and individuals, we find evidence that high-quality inventions are sold under preemptive bidding competition. Asymmetric information problems are shown to be solved by verification through entry for sale.
Keywords: G24; L10; L20; M13; O30; 330; acquisitions; entrepreneurship; innovation; start-ups; patent; ownership; quality; Innovation; Patent; Unternehmensgründung; Kommerzialisierung; Schumpeterismus; Übernahme; Probit-Modell; Theorie